Translating the theory into practice : the collating, comparing and synthesising of foundational recommendations and qualities for restorative garden design - Schwarz, Sandra (SLU/Dept. of People and Society, 2019)
The catalyst for this Thesis was a recognised ‘disconnect’ between academic research and landscape architects / designers of restorative green spaces, which was validated by several experts in the field. The need for research to provide tangible recommendations and examples of best practice, in the principle of Evidence-based Design, drove this task. A literature study informs background knowledge of the main theories within this field, namely Appleton, the Kaplans, Ulrich and Grahn & Stigsdotter. Beyond these foundational theories the literature was examined and synthesised via the use of matrices to result in a set of 10 categories and their connected qualities, which benefit and support restorative green spaces. This analysis has resulted in the broad conclusion that the most ideally recommended setting for restoration is one that provides a range of spaces from which to choose, set within a lush and diverse natural landscape that encourages birdsong and other multi-sensory stimulation. The recommendations have also been visually presented through a range of case studies within both stress rehabilitation and cancer care. The recommendations resulting from this work have the potential to be used for Post-occupancy Evaluation in future, but primarily they constitute a sound practical basis for restorative green space design, onto which discussions with client, user and specific context should be built. The work thereby provides a solid foundation for informed design of restorative green spaces in future practice.